Molnupirvir-induced SARS-CoV-2 mutagenesis mechanism and results of this antiviral in patients affected by COVID-19 (Research, Society and Development, 2021)
Introduction: Antiviral drugs often target viral polymerases and function as nucleoside analogues that terminate the elongation of the RNA chain. However, such chain-terminating antivirals are generally not effective against SARS-CoV-2, as coronaviruses carry an exonucleolytic proofreading activity, which can thus remove improperly incorporated nucleotides from the ends of RNAs. Objective: to elucidate the mutagenic mechanisms of SARS-CoV-2 induced by molnupirvir, as well as to couple the results of the use of this antiviral in patients affected by COVID-19. Methodology: This is a systematic literature review and the following keywords were crossed: "molnupiravir", "COVID-19", "SARS-CoV-2", "antiviral", "RNA" in the following bases data: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services. Relevant sources inherent to the theme were analyzed, using as one of the main criteria the choice of current, original and international articles. After careful reading of the publications, 4 articles were not used due to the exclusion criteria. Thus, there were a total of 12 scientific articles for review. Results: Molnupiravir or NHC can increase G to A and C to U transition mutations in coronavirus replication. These increases in mutation frequencies may be associated with increases in antiviral effects; however, no biochemical data of molnupirvir-induced mutagenesis have been reported. Here we study the effects of the active compound NHC 5'-triphosphate (NHC-TP) against the purified severe acute respiratory syndrome coronavirus 2 RNA-dependent RNA polymerase complex. In addition, molnupiravir has demonstrated in vitro activity against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in cultures of human airway epithelial cells. Conclusion: a promising candidate for the treatment of these patients is molnupiravir (or EIDD-2801), which also targets RdRp of SARS-CoV-2, interferes with virus replication, inhibiting SARS-CoV-2 replication in tissue human lung and blocking its transmission.